Impact of Adult Popillia japonica (Coleoptera: Scarabaeidae) Foliar Feeding Injury on Fruit Yield and Quality of a Temperate, Cold-Hardy Wine Grape, ‘Frontenac' - Ebbenga, Dominique N.; Burkness, Eric C.; Clark, Matthew D.; Hutchison, William D. (Frontiers in Insect Science, 2022)
Popillia japonica (Newman), is a highly polyphagous, invasive species, first recorded in the U.S. in 1916, and detected in Minnesota in the late 1960s. Historically, research on this pest in the Midwest U.S. has focused primarily on ornamental and turf crops, with little attention placed on adult feeding damage to fruit crops. Recently, wine grape producers in the region noted substantial increases in defoliation from P. japonica feeding, confirming concerns for this perennial high value crop. To address these concerns, studies were conducted during the summers of 2020-2021 to understand the impact of P. japonica foliar feeding on the quality and yield of wine grapes. Trials utilized vines of the wine grape variety, ‘Frontenac’. In addition to open plots, whole vines were caged within fine mesh netting and infested with P. japonica at 0, 25, 50, and 100 beetles per meter-row of vine. Beetles used for infestations were collected from natural field populations of P. japonica and left to feed until grapes were ready for harvest. During harvest, data collection included leaf samples for obtaining average percent defoliation, cluster weights, and berry subsamples for soluble solid content, pH, titratable acidity, and phenolic compound measurements. Results from these studies demonstrated that as beetle population density and defoliation per m-row increases, at-harvest measurements of quality parameters are significantly and negatively affected (P<0.05) when compared with uninfested vines. The negative impacts to fruit quality exhibited in these studies will be important in the development of future management strategies for P. japonica in ‘Frontenac’.